The satisfaction with sex life scale - Felix Neto (2012)
The purpose of this article was to develop the Satisfaction With Sex Life Scale (SWSLS). Scores from the SWSLS have favorable psychometric properties. Cronbach's alpha was .92. Evidence based on relations to other variables was examined. Suggestions concerning the use of the SWSLS for research and clinical purposes are offered.